EL ORIGEN DE LA VIDA EN LA TIERRA: UN MISTERIO QUE PERDURA. - VICUÑA, RAFAEL (Humanitas (07172168))
The origin of life on Earth is a mystery that persists, challenging scientists. Despite partial advances, the origin of life remains an enigma. Various perspectives on the subject include divine intervention, almost miraculous events, inevitable determinism, and the work of a supernatural Creator through natural causes. The irreducible complexity and specific information of life are indicative of a supernatural mind responsible for it. Despite advances in research, there are still challenges in understanding the origin of life on Earth.